Law relating to patents, trade marks, copyright designs & geographical indications - Wadehra, B. L. (Basant Lal), 1927- (Delhi : Universal Law Pub. Co. : Distributors, Universal Book Traders, 2017)
Includes reference to India and Indian case laws.
Includes index.
Keywords: Intellectual property -- India; Intellectual property -- India -- Forms